IN-ORBIT IMPLEMENTATION OF ERROR PATCHING METHODS FOR LAPAN-A3/IPB OBDH FIRMWARE SYSTEM - Taufik, Muhammad; Hasbi, Wahyudi; Karim, Abdul (BRIN Publishing, 2019)
OBDH (On-board data handling) is a satellite subsystem that receives, processes, decides and executes commands from and to satellites. OBDH is built on two systems namely hardware and software integrated system (firmware system). In terms of hardware, OBDH uses a processor with 32bit RISC architecture, 128/256 Kbyte internal memory and a firmware system that is built using primitive programming. This programming uses the super loop architecture program and interrupt to manage the system to function properly. Problems occur when an error occurs in one of the functions in the interrupt routine resulting in failure of interpretation of commands or data from satellite sensors. This paper describes the implementation of the error patching methods on the LAPAN-A3/IPB Satellite OBDH firmware system in order to keep the system working well. Initial verification through testing on the ground have been successfully performed using engineering model of OBDH and hardware in the loop simulators (HWIL) module. Based on the test results, implementation on satellite has also been successfully done.